Comparative clinical impact of low-curvature and normal-curvature titanium mesh in cranioplasty: a retrospective analysis of patient outcomes - Yang, Shengkai; Chen, Weihua; Teng, Hongwei; Zhang, Lei; Ji, Kangkang; Zhou, Hai (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to evaluate the clinical utility of two types of cranioplasty surgery involving low-curvature and normal-curvature titanium mesh, respectively.MethodsThe clinical data were retrospectively collected from patients undergoing skull defect repair surgery between January 2021 and December 2022. The clinical outcomes associated with the two surgical approaches were compared and analyzed.ResultsA total of 67 patients who underwent skull defect repair surgery were enrolled, with 22 in the low-curvature titanium mesh group and 45 in the normal-curvature titanium mesh group. Both before and after propensity score matching (PSM) analysis, the hospital stay for the low-curvature titanium mesh group was significantly shorter than that for the normal-curvature mesh group (Before: 9.14 ± 2.64 vs. 12.51 ± 4.15, P = 0.001; After: 9.44 ± 2.83 vs. 12.13 ± 4.40, P = 0.048). The low-curvature group exhibited lower overall hospitalization costs than the normal-curvature group (Before: 23500. ± 900. vs. 24,900. ± 1,100., P < 0.001; After: 23,300. ± 800. vs. 24,100. ± 1,000., P = 0.026). Moreover, satisfaction with molding (Before: 4.23 ± 0.75 vs. 3.18 ± 0.81, P = 0.001; After: 4.13 ± 0.72 vs. 3.25 ± 0.78, P < 0.001), Karnofsky's Performance Status score (Before: 93.32 ± 1.67 vs. 90.38 ± 3.50, P = 0.001; After: 93.56 ± 1.75 vs. 91.00 ± 3.78, P < 0.001), and Quality of Life score (Before: 52.95 ± 2.13 vs. 50.18 ± 3.54, P = 0.001; After: 53.31 ± 2.12 vs. 50.38 ± 4.23, P = 0.001) were significantly higher in the low-curvature titanium mesh group than the normal-curvature titanium mesh group.ConclusionsApplying low-curvature titanium mesh for skull repair effectively shortens the hospital stay, reduces overall hospitalization costs,enhances patient satisfaction with surgical modeling, and improves the postoperative functional status and quality of life of patients undergoing neurosurgery. These advantages warrant further clinical promotion.